Food choice motivations and perceptions of healthy eating: a cross-sectional study among consumers in the UAE - Leila Cheikh Ismail; Tareq M. Osaili; Reyad Shaker Obaid; Mona Hashim; Marya Ahmed; Fatma Al-Fayadh; Aisha Farah; Hanin Sad; Humood Alghanem; Maysm N. Mohamad; Sheima T. Saleh; Rameez Al Daour; et al. (BMC Public Health)
Abstract Background Investigating consumer food choice motivations is crucial for planning effective policies and targeted interventions. This study aimed to examine the food choice motivations and perceptions of healthy eating among adults in the United Arab Emirates (UAE) and to segment consumers based on their motivations. Methods A web-based, cross-sectional study was conducted among adults in the UAE (n = 1209). An overall perception of healthy eating score was calculated based on the sum of the responses to the perception statements. Food motivation scores were calculated with a higher score indicating more influence of the food motivation group. Hierarchical Cluster Analysis (HCA) and K-means cluster analysis were used to identify and determine the optimal number of clusters. Differences between clusters were evaluated using an Independent sample t-test, One-Way ANOVA test, and Chi-square analysis. Results Participants mostly agreed that a healthy diet should be balanced, varied, and complete (84.4%), that fruit and vegetables are essential to a practice of healthy eating (82.8%), and that they can eat everything as long as it is in small quantities (60.1%). Females, younger adults, those with higher education levels, and those with normal BMI tended to have a slightly more positive perception of a healthy diet than their counterparts (p < 0.05). Health motivation (mean = 3.43, SD ± 0.78) exhibited the highest influence on the participants’ food choices, followed by emotional motivations (mean = 3.26, SD ± 0.68). Health-related motivations mainly influenced food choices among participants in both identified clusters but were notably more emphasised in Cluster 1. Cluster 1 demonstrated significantly higher mean scores in all other categories than Cluster 2 (p < 0.001). Cluster 1 encompasses more female participants than males, while Cluster 2 comprises a more significant proportion of males and individuals falling within higher income brackets (p < 0.001). Conclusions The results of the current study offer valuable insights into various crucial aspects that impact the decisions of individuals' food choices. Based on distinct motivational structures identified through cluster analysis, personalised approaches can encourage healthier dietary practices. A holistic approach acknowledging emotional, economic, environmental, alongside health-related factors is vital.